2022
DOI: 10.4018/ijdsgbt.313954
|View full text |Cite
|
Sign up to set email alerts
|

Information Privacy Assimilation

Abstract: This paper proposes a framework to understand organizations' perspectives while safeguarding customers' information privacy. Following a detailed literature review, a broad conceptual model was developed to build a theory based on a multi-site, multi-case study approach. The current manuscript treats information privacy as distinct from information security. From an organizational standpoint, this research reveals that legal policy, technology, and industry standards drive privacy assimilation. At a detailed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(65 reference statements)
0
0
0
Order By: Relevance
“…Technological change rates are crucial, as Chatterjee et al (2022) found that technological turbulence negatively impacts automated decision-making and operational efficiency in business-to-business relationships. Furthermore, resistance to compliance, investment costs, and a reactive approach to privacy practices pose additional challenges, underlining the need for a RAI approach to address these issues effectively (Halder et al, 2022).…”
Section: Literature Review the Need For Ai Governance Within The Companymentioning
confidence: 99%
See 1 more Smart Citation
“…Technological change rates are crucial, as Chatterjee et al (2022) found that technological turbulence negatively impacts automated decision-making and operational efficiency in business-to-business relationships. Furthermore, resistance to compliance, investment costs, and a reactive approach to privacy practices pose additional challenges, underlining the need for a RAI approach to address these issues effectively (Halder et al, 2022).…”
Section: Literature Review the Need For Ai Governance Within The Companymentioning
confidence: 99%
“…Recent technological advancements in AI, cloud computing, 5G, and Web3 necessitate either more regulatory actions, which may include laws, regulations, and antitrust initiatives, or more international data standards, improved data architecture, and greater interoperability of data via improved interfaces (Dąbrowska et al, 2022). The findings of Halder et al (2022) underscored the influence of legal policy on organizations' privacy practices, emphasizing the pivotal role of legal frameworks in shaping responsible AI governance. The relevant legal frameworks for AI will depend on the specific context and application of AI challenges or following national or international laws.…”
Section: Legal Dimensionmentioning
confidence: 99%